Exploring the Words relating to People and Places in the Correspondence of two British Women Travellers - Ditifeci, Francesca (Status Quaestionis, 2024)
This study focuses on the language used by two British women travellers in their letters – Lady Lucie Duff Gordon in Letters from Egypt (1865), Lady Hilda Petrie in Letters from the Desert (1942). Lexical keywords are analysed in order to compare and contrast the authors’ attitude towards Egyptian people and places, and assess whether and to what extent any shift in point of view can be seen as an expression of the changed socio-historical context and/or it also involves the authors’ attitude in their role as women explorers. The article combines quantitative and qualitative analysis of epistolary discourse, with special attention to the presence (vis-à-vis absence of) evaluative language (Hunston and Thomson 2000). The data suggest different ways of looking at Egyptian people and places. Particularly, whereas Duff Gordon seems very interested in the region she has settled in and particularly in its inhabitants, Petrie seems to be predominantly interested in reporting about places seen as archaeological sites.